2023
DOI: 10.1186/s12909-023-04793-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulation in improving the self-confidence of student nurses in clinical practice: a systematic review

Nojoud Alrashidi,
Eddieson Pasay an,
Maha Sanat Alrashedi
et al.

Abstract: Background Considering the positive influence of simulation from previous literature may encourage educators to regard it as a valuable teaching strategy in nursing schools. This literature review aims to investigate whether the use of simulation improves undergraduate nurses’ self-confidence during clinical practice. Methodology This study employed a literature-based design. Five academic databases, including CINAHL, EBSCO, ProQuest, PubMed and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Several studies found that simulated patient-based training endows students with high levels of self-confidence by improving their clinical competencies and communication skills in psychiatric settings and enhancing their abilities to carry out clinical tasks and abilities to work in teams. Moreover, the participating students felt confident and prepared for real-world encounters with mental health patients [ 21 , 24 , 26 , 27 , 28 , 29 , 30 ]. Meanwhile, Johnson et al [ 25 ] reported that using standardized patient simulation for first-semester nursing students was not effective in improving their self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that simulated patient-based training endows students with high levels of self-confidence by improving their clinical competencies and communication skills in psychiatric settings and enhancing their abilities to carry out clinical tasks and abilities to work in teams. Moreover, the participating students felt confident and prepared for real-world encounters with mental health patients [ 21 , 24 , 26 , 27 , 28 , 29 , 30 ]. Meanwhile, Johnson et al [ 25 ] reported that using standardized patient simulation for first-semester nursing students was not effective in improving their self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] It has been well documented that increased exposure to clinical skills improves competency, improving patient care. [ 3 4 ] However, training on actual patients is challenging due to ethical issues and practical limitations. Thus, the need of the hour is to facilitate learning in an environment close to real-time situations to acquire the required competent skills.…”
Section: Introductionmentioning
confidence: 99%
“…Standardized patient simulation, in particular, plays a crucial role in creating immersive and realistic scenarios in nursing education [8,9]. Integrating standardized patients into simulation-based nursing education significantly enhances the authenticity and consistency of scenarios, allowing the transfer of theoretical knowledge to practical settings [10,11]. This approach facilitates the development of essential skills and competencies while also fostering a deep understanding of the art and essence of nursing by acknowledging the holistic nature of human beings and delivering patient-centered care [11].…”
Section: Introductionmentioning
confidence: 99%
“…This approach facilitates the development of essential skills and competencies while also fostering a deep understanding of the art and essence of nursing by acknowledging the holistic nature of human beings and delivering patient-centered care [11]. Previous studies have demonstrated the effectiveness of simulation-based nursing education in developing a wide range of skills and competencies crucial for nursing practice, including developing practical skills, reacting and thinking in real situations, communication skills, clinical practice competency, empathy, and self-confidence to provide humanized nursing care [10,12].…”
Section: Introductionmentioning
confidence: 99%